2016
DOI: 10.21037/jtd.2016.12.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changing from the National Health and Nutritional Examination Survey III spirometry reference range to that of the Global Lung Initiative 2012 at Gold Coast Hospital and Health Service

Abstract: The categorisation of lung disease into obstructive ventilatory defect (OVD) and tendency to a restrictive ventilatory defect (TRVD) patterns using spirometry is used to guide both prognostication and treatment. The effectiveness of categorisation depends upon having reference ranges that accurately represent the population they describe. The Global Lung Initiative 2012 (GLI 2012) has spirometry reference ranges drawn from the largest sample size to date. This study aimed to determine whether using spirometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Our results are comparable to previous findings demonstrating that the rates of severity classification of AO were changed when changing from the Korean (Lee and Choi) to Caucasian (Morris and Knudson) reference equations (15). Other studies also showed that the rates of severity classification were changed when changing from the NHANES III to the GLI2012 reference equations in a Caucasian population (21,24).…”
Section: Chaiwong Et Al Effect Of Changing Spirometry Referencesupporting
confidence: 87%
“…Our results are comparable to previous findings demonstrating that the rates of severity classification of AO were changed when changing from the Korean (Lee and Choi) to Caucasian (Morris and Knudson) reference equations (15). Other studies also showed that the rates of severity classification were changed when changing from the NHANES III to the GLI2012 reference equations in a Caucasian population (21,24).…”
Section: Chaiwong Et Al Effect Of Changing Spirometry Referencesupporting
confidence: 87%
“…Another study suggested that changing from the Stanojevic to the GLI2012 reference equations caused an increase of 32% in the rate of AO [10]. However, the other studies showed a concordance of the diagnosis associated with AO when changing between the NHANES III and GLI2012 [10,12,16,17] due to the higher LLN value of the FEV1/FVC ratio in the Siriraj reference equation when compared to the GLI 2012 reference equations. Thus, the differences in the rate of diagnosis associated with AO between the two references equations are likely to have occurred when the ratio of FEV1/FVC was close to the LLNs values.…”
Section: Discussionmentioning
confidence: 99%
“…The GLI 2012 has also been recommended for use in every country, including Thailand. Previous studies have shown a concordance in the diagnosis associated with AO when using the GLI2012 and the Third National Health and Nutrition Examination Survey (NHANES III) [10,11,12,13], the European Community for Steel and Coal (ECSC) [11], and the Zapletal [14]. However, there is some discordance in the interpretation of AO when changing from the ECSC [10,14,15], and the Stanojevic [10] to the GLI2012.…”
Section: Introductionmentioning
confidence: 99%
“…The Global Lung Function Initiative (GLI) has produced spirometry reference equations for use in different ethnic groups from early childhood to the elderly years . Previous reports have shown that the GLI equations do not adequately describe lung function in all populations and that adopting the new equations into clinical practice can increase the number of patients considered to have abnormal lung function . Therefore, before adopting these equations into local practice, especially in communities not included in the GLI project, it is necessary to establish how well the equations represent the local population …”
Section: Introductionmentioning
confidence: 99%
“…2 Previous reports have shown that the GLI equations do not adequately describe lung function in all populations 3,4 and that adopting the new equations into clinical practice can increase the number of patients considered to have abnormal lung function. 5 Therefore, before adopting these equations into local practice, especially in communities not included in the GLI project, it is necessary to establish how well the equations represent the local population. 6 The present study was conducted to determine how well the GLI spirometry reference equation represented the young children in Argentina, a population not included in the GLI dataset, and to determine whether adoption of these equations would lead to misrepresentation of lung disease in local children.…”
Section: Introductionmentioning
confidence: 99%